Implementation of spatial SV wave oblique incidence and helical pile response under this condition based on Python in finite element analysis - Hang Cen; Hui-yue Wang; Wen Zhou; De-long Huang; Zhong-ling Zong; Sha-sha Yu; Chang-lu Xu; Zi-yuan Huang (AIMS Geosciences)
The traditional method of adding viscoelastic artificial boundaries and equivalent seismic loads has the disadvantages of a cumbersome adding process and a difficulty in finding errors. Therefore, this paper was based on the existing theory and derived the spatial oblique incidence equivalent node load method on this basis, integrating the ground stress equilibrium, dynamic stress equilibrium, and equivalent seismic load and boundary application into one plug-in. The oblique incidence of spatial SV waves was simulated using the finite element method, and its accuracy was validated through comparison with analytical results. Subsequently, the feasibility of the oblique incidence simulation method was further demonstrated through the use of pile foundation seismic subsidence response cases. Based on the three factors of seismic wave type, peak ground acceleration, and oblique incidence angle, the dynamic response of the helical piles was analyzed in depth, which confirmed that the effect of oblique incidence on the structure in the soil should not be neglected. This approach significantly reduces modeling time and establishes a solid foundation for analyzing the dynamic response of structures in geotechnical fields.